2018
DOI: 10.1177/1541931218621329
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Impact of Training and Feedback on Visualization-Supported Decision Making under Uncertainty

Abstract: Empirical evaluations of uncertainty visualizations often employ complex experimental tasks to ensure ecological validity. However, if training for such tasks is not sufficient for naïve participants, differences in performance could be due to the visualizations or to differences in task comprehension, making interpretation of findings problematic. Research has begun to assess how training is related to performance on decision-making tasks using uncertainty visualizations. This study continues this line of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The present study has two overarching goals. First, this study aims to replicate recent findings emphasizing the importance of training in uncertainty visualization research (e.g., Fiore et al, 2019;Song et al, 2018). In doing so, we contribute to this growing area of research on how to improve the design of empirical evaluations of uncertainty visualizations.…”
Section: Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…The present study has two overarching goals. First, this study aims to replicate recent findings emphasizing the importance of training in uncertainty visualization research (e.g., Fiore et al, 2019;Song et al, 2018). In doing so, we contribute to this growing area of research on how to improve the design of empirical evaluations of uncertainty visualizations.…”
Section: Methodsmentioning
confidence: 70%
“…This highlights the importance of understanding how varying forms of training may influence task comprehension and potentially distort the apparent effectiveness of uncertainty visualizations. However, a related study found that regardless of variations in training administration, participants who demonstrated relatively high training comprehension outperformed those who demonstrated relatively low training comprehension (Song et al, 2018). In addition to considering differences in decision making and task familiarity between experts and non-experts, we also propose that equal consideration should be given when it comes to differences within non-expert participant samples.…”
Section: Uncertainty Visualization Challengesmentioning
confidence: 89%
See 1 more Smart Citation
“…When considering VR simulators for testing, they may provide an additional diagnostic capable of better predicting training efficacy. For example, previous research shows that different types of knowledge acquisition assessments predict transfer performance on complex decision-making tasks (Fiore et al, 2002;Song et al, 2018). Recently, Song and colleagues (2019) found that training comprehension was predictive of complex transfer-type tasks assessing decision making under uncertainty.…”
Section: Introductionmentioning
confidence: 99%